Potential Role of Regional Railways in Regional Transportation - Szabó, L. (Acta Technica Jaurinensis, 2011)
Beside Hungarian Railways Plc (MÁV) and other railway companies, local railways companies contributed to forming the railway network in Hungary. The establishment of local railways was legally supported by the Article XXXI/1880 and Article IV/1888. The operation of local railways between Arad – Körös region was allowed before these laws came into effect. The constructions of local railways had a considerable pace as 57% of them were built by local railway companies in 1918. The laws set simple technical conditions to start the constructions resulting in lower construction costs. The lines built with lower technical quality still met the requirements of local transport. Local railway companies became completely state owned after 1945, except for Local Railways Plc of the Fertő region. However, many of the former local rail lines were closed. Most of the currently functioning branch lines are actually the former local railways. The railways which had not been closed had worse and worse technical conditions with a declining number of passengers. In most of the cases the solution was to close rail lines with bad infrastructure parameters. The present study outlines a model appropriate for a complex analysis of problems of branch lines while considering potential roles of rail lines in regional transport.